Investigation of reactor temperature and performance of syngas cooling system for vacuum gasification of soaked biomass - Novandri Tri Setioputro; Muhtar Kosim; Kasda; Ronald Sukwadi; Widodo Widjaja Basuki; Dede Iman Saputra (Case Studies in Thermal Engineering, 2023)
Vacuum-soaked biomass gasification is a method being developed to replace fossil fuels in a safe, simple, and reliable manner. The biomass gasification process demands high temperatures in the region of 800–1000 °C, yet even when applying vacuum pressure and soaking the biomass, the experimental results of the gasification temperature can be maintained properly. Cyclone and heat exchanger system, the reactor's syngas exit temperature, which is typically 600 °C, and may be lowered to under 50 °C. The heat exchanger's temperature profile indicates that 8 m are the most practical/ideal length. The heat exchanger's effectiveness is almost perfect (0.99) and higher than in earlier experiments (0.43–0.55). The use of an open-water jacket improves the performance of the heat exchanger by lowering the LMTD by 33.60% and lowering the heat transfer rate by 24.55%. Open-water life jackets do not significantly improve effectiveness.